2017
DOI: 10.1007/s40544-017-0181-7
|View full text |Cite
|
Sign up to set email alerts
|

Tribology of multilayer coatings for wear reduction: A review

Abstract: Friction and wear phenomena encountered in mechanical systems with moving components are directly related to efficiency, reliability and life of the system. Hence, minimizing and controlling these phenomena to achieve the desired system performance is crucial. Among the numerous strategies developed for reducing friction and wear, coatings have been successfully utilized in various engineering applications to mitigate tribological problems. One of the benefits of coatings is that they may be fabricated using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(96 citation statements)
references
References 67 publications
0
95
0
1
Order By: Relevance
“…From the very moment of the first mention of these structures to the present, researchers have collected a lot of information about the deposition techniques, structure, properties and further perspectives of application. It was found that binary metal nitrides exhibit improved characteristics compared to conventional metals [9][10][11][12][13]. Furthermore, multilayer nitride coatings demonstrate excellent durability, wear and corrosion resistance, mechanical, optical, electronic and magnetic properties [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the very moment of the first mention of these structures to the present, researchers have collected a lot of information about the deposition techniques, structure, properties and further perspectives of application. It was found that binary metal nitrides exhibit improved characteristics compared to conventional metals [9][10][11][12][13]. Furthermore, multilayer nitride coatings demonstrate excellent durability, wear and corrosion resistance, mechanical, optical, electronic and magnetic properties [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Covalent nitrides can be formed by the bonding of nitrogen with the metal and non-metal atoms that have electrons in p-orbital (B, Al, Si, Ga, Ge, etc.). Nitrides of transition metals, which are characterized by partly filled d-or f-shells, consist of nitrogen (solute atom) that is placed in the crystalline lattice of the host transition metal [9]. They have quite complex composition, which does not correspond to the common oxidation states (TiN, ZrN, Cr 2 N, Mn 3 N 2 ), moreover, transition metals form in some cases several forms of nitrides, for example Nb 2 N and NbN, Ta 2 N, Ta 3 N 5 and TaN and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…There are several paths to their design: depositing a set of films in a special order according to their functionality (e.g., substrate > adhesion film > superhard film > oxidation resistant film), alternating films with a similar crystal lattice for epitaxial growth, hard crystalline films with thin amorphous layers, alternating TMN, TMC or TMB films, nanocomposites, HEAs coatings, etc. Many research groups around the world have worked on this topic, and many papers have been published that review and evaluate the recent progress in this area [127,133,155,[158][159][160]. Among the most recent and interesting multilayer solutions for protective coatings there are TiN/TiAlN [161,162], TiAlN/TaN [163], Ti(Al)N/Cr(Al)N [121], (TiAlSiY)N/MoN [164], CrN/AlSiN [165], AlCrN/TiAlTaN [166], TiSiC/NiC [167], TiN/MoN [168,169], TiN/WN [170], TiN/ZrN [171], Zr/ZrN [172], Ta/TaN [173], CrN/MoN [174][175][176], (TiZrNbHfTa)N/WN [177], and multilayer hard/soft DLC coatings [178].…”
Section: Multi-layered and Graded Coatingsmentioning
confidence: 99%
“…Багатокомпонентні, багатошарові та функціонально-градієнтні покриття знаходять все більш широке використання у різних галузях промисловості [1,2]. Тому розробка нових технологій формування таких покриттів безумовно є актуальною.…”
Section: вступ мета роботиunclassified